Lactate on emergency department arrival as a predictor of mortality and site-of-care in pneumonia patients: a cohort study. Issue 5 (23rd February 2015) - Chen, Yun-Xia; Li, Chun-Sheng
Abstract : Objective: To investigate the predictive performance of lactate, CURB-65, and a combination of lactate and CURB-65 (LAC-CURB-65) for mortality, hospitalisation and intensive care unit (ICU) admission in pneumonia patients in the emergency department (ED). Methods: Consecutive adult patients with pneumonia presenting from January 2012 to May 2014 were divided into low-, moderate- and high-risk groups according to lactate (<2.0, 2.0–4.0, >4.0 mmol/L), CURB-65 (≤1, 2, ≥3) and LAC-CURB-65 (patients with two low risks, any moderate risk, any high risk) values. Mortality, hospitalisation and ICU admission rates were compared between risk classes. Results: Of 1641 patients, 861 (53%) were hospitalised (38% to a general ward, 15% to the ICU) while the remaining 780 (47%) were treated as outpatients or observed in the ED. 547/1641 (33%) patients died within 28 days. Lactate and CURB-65 were higher in patients who died, were hospitalised or were admitted to the ICU compared with patients who were not (p<0.001). Lactate and CURB-65 independently predicted outcomes. The performance of lactate in predicting 28-day mortality, hospitalisation and ICU admission was higher than that of CURB-65 (p<0.01). For LAC-CURB-65, patients at low or moderate risk had mortality rates of 2% and 14%, respectively, and hospitalisation rates of 15% and 40%, respectively, while none were admitted to ICU. Patients at high risk had the highest mortality (52%), hospitalisation (70%) and ICU admission rates (27%). Conclusions: Lactate is superior to CURB-65 in predicting mortality, hospitalisation and ICU admission in pneumonia patients in the ED. LAC-CURB-65 significantly improved the predictive value of CURB-65.